Microscopic morphology, rheological behavior, and mechanical properties of polymers: Recycled acrylonitrile‐butadiene‐styrene/polybutylene terephthalate blends. Issue 4 (31st July 2019) - He, Hezhi; Zhan, Zhiming; Zhu, Zhiwen; Xue, Bin; Li, Jiqian; Chen, Ming; Wang, Guozhen
ABSTRACT: In this study, styrene‐acrylonitrile‐glycidyl methacrylate (SAG) series copolymers were specially designed for producing the recycled acrylonitrile‐butadiene‐styrene (rABS)/poly(butylene terephthalate) (PBT)/SAG blends, which were prepared through the process of continuous melt blending and batch feeding. The effects of viscosity composition, SAG chemical composition, and SAG content on the morphology, and rheological and mechanical properties of the blends have been investigated. As demonstrated by morphological observation, the variety of viscosity composition of the blends affects the size of dispersed PBT droplets. Moreover, high viscosity of rABS matrix seems to facilitate the formation of smaller dispersed phase size of blends. Various SAG chemical compositions have different stabilities on the morphology of the blends, which affects the deformation, fragmentation, and coalescence of dispersed phase droplets. In addition, a finer phase morphology can be achieved when the density distribution of epoxy group is optimal in SAG copolymer. Rheological characterization manifested that the rheological properties of the blends depends strongly on its composition and structure, while the crosslinking degree is associated with the concentration of reactive groups and extent of reaction. Thereby, the rheological behavior of the blends during processing can be controlled by changing the reactive sequence and adding the quantity of epoxy group. The test on mechanical properties verified that a recycled product with excellent performance can be obtained by altering processing methods and the blends formula, which may be further applied to the 3D printing materials required by fused deposition modeling technology. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48310. Abstract :